Diversity of root bacterial community associated with seven orchid species from Mount Merbabu National Park, Central Java, Indonesia - ARTINI PANGASTUTI; ARI PITOYO; ARI SUSILOWATI; RIZKA MEISARI; IRVY YULIANA; KHATSANATUL AULIA; LIANA PUTRI PUSPITASARI; RUSIANI RUSIANI; HENDRO PRASOJO (Society for Indonesian Biodiversity, 2023)
Abstract. Pangastuti A, Pitoyo A, Susilowati A, Meisari R, Yuliana I, Aulia K, Puspitasari LP, Rusiani, Prasojo H. 2023. Diversity of root bacterial community associated with seven orchid species from Mount Merbabu National Park, Central Java, Indonesia. Biodiversitas 24: 5676-5684. Indonesia has a high diversity of wild orchids. One of the orchid habitats that has not been widely explored is Mount Merbabu National Park (TNGMb), Central Java, Indonesia. The dependence of orchids on specific microorganisms for survival and growth, especially during early development, has not been widely studied. Endophytes, such as bacteria, can help the host plant grow, tolerate stress, resist disease, acquire nutrients, or form symbiotic relationships. However, bacterial endophytes associated with orchids have not been extensively explored. This research examined the diversity of bacteria associated with orchid roots in Mount Merbabu National Park using a culture-independent method. Seven orchid species were sampled for root bacterial community analysis, that identified as Spathoglottis plicata, Dendrobium sagittatum, Malaxis kobi, Apendicula alba, Pholidota carnea, Dendrobium tenellum, and Bulbophyllum compressa. Bacterial diversity in all orchid roots was high, with several dominant bacterial species. Proteobacteria, Firmicutes, Bacteriodota, and Actinobacteriota were the four most abundant phyla, with Proteobacteria having the highest abundance (37 to 90%) in all samples. The top ten bacteria genera were Pseudomonas, Serratia, Rhodanobacter, Acinetobacter, Escherichia, Bifidobacterium, Clostridium, Parabulkholderia, Faecalibacterium, and Muribaculaceae family that could not be identified at the genus level. Overall, 61, 42, 838, 98, 78, 973, and 1383 OTUs were unique to S. plicata, D. sagittatum, M. kobi, A. alba, P. carnea, D. tenellum, and B. compressa, respectively, whereas all seven species shared 335 OTUs. Our research suggested that environmental factors and the host plant's genetics affect the plant microbiome's composition and diversity. These elements might be essential for ecosystem function and conservation.